ANALYSIS AND EVOLUTION OF THE CATACOMB STRUCTURE OF THE ALANIAN CULTURE ON THE MIDDLE TEREK FROM THE 3RD TO THE MID-5TH CENTURY AD - Malasev, Vladimir Ur'evic (History, Archeology and Ethnography of the Caucasus, 2024)
Archaeological excavations at the Bratskiye I, Oktyabrskiy I, and Kievskiy I burial grounds conducted in 2018–2019 yielded 323 burial complexes belonging to the Alanian culture, dating from the 3rd century to the first half/middle of the 5th century AD. The predominant burial structure identified was Type I catacomb, accounting for 90% (290 complexes) of the analyzed sample. These catacombs were examined for structural changes across four chronological periods: the first half – middle of the 3rd century AD; the second half of the 3rd – early 4th century AD; the first – third quarter of the 4th century AD; the last quarter of the 4th – first half/middle of the 5th century AD. The following features were analyzed: the shape and orientation of the entrance pits, their proportions, the design of the steps at the rear walls of the entrance pits, the shape of the entrance to the chamber, the length of the dromos, the shape and orientation of the chambers, and the shape of the vault. This analysis allowed us to observe their evolution over the identified periods and to establish three standards with one transitional group, each with a chronological assessment: standard I (first half to the middle of the 3rd century AD); standard II (4th century AD); and standard III (around the turn of the 4th/5th centuries to the first half/middle of the 5th century AD). The transitional group (second half of the 3rd century AD) occupies an intermediate position between standards I and II, wherein half of the features align with standard I, and half with standard II; within this framework, changes in certain features occur, followed by the development of a new standard. To summarize, the following trends were observed: 1) The shape of the entrance pits changed from trapezoidal to rectangular, and their proportions elongated; 2) The design of the steps evolved from various combinations of corner steps to steps in the form of a staircase from one corner of the entrance pit along the side wall, and later to steps at the back wall along the entire width of the entrance pit; 3) The shape of the chambers changed from oval to rectangular; 4) The shape of the vault changed from descending from the entrance to the front wall of the chamber and horizontal – to extended from the entrance upwards, pointed, and, less often, trapezoidal; 5) There was a general increase in the degree of standardization from the 3rd century to the first half/middle of the 5th century AD.
Keywords: Alanian culture; Middle Terek; 3rd – first half / middle of the 5th century AD; catacombs of Type I; construction design